Prognostic relevance of the C-X-C motif chemokine ligand 13 and interleukin-8 in predicting the transition from clinically isolated syndrome to multiple sclerosis - Klíčová, Kateřina; Mareš, Jan; Sobek, Ondřej; Rous, Zuzana; Rous, Matouš; Raška, Milan; Hartung, Hans-Peter (The European journal of neuroscience, 2024)
The initial phase of multiple sclerosis (MS), often known as clinically isolated syndrome (CIS), is a critical period for identifying individuals at high risk of progressing to full-blown MS and initiating timely treatment. In this study, we aimed to evaluate the prognostic value of C-X-C motif chemokine ligand 13 (CXCL13) and interleukin-8 (IL-8) as potential markers for CIS patients' conversion to MS. Our study encompassed patients with CIS, those with relapsing-remitting MS (RRMS), and control subjects, with sample analysis conducted on both cerebrospinal fluid (CSF) and serum. Patients were categorized into four groups: CIS-CIS (no MS development within 2 years), CIS-RRMS (conversion to RRMS within 2 years), RRMS (already diagnosed), and a control group (CG) with noninflammatory central nervous system disorders. Results showed significantly elevated levels of CXCL13 in CSF across all patient groups compared with the CG (p < 0.0001, Kruskal-Wallis test). Although CXCL13 concentrations were slightly higher in the CIS-RRMS group, statistical significance was not reached. Similarly, significantly higher levels of IL-8 were detected in CSF samples from all patient groups compared with the CG (p < 0.0001, Kruskal-Wallis test). Receiver operating characteristic analysis in the CIS-RRMS group identified both CXCL13 (area under receiver operating characteristic curve = .959) and IL-8 (area under receiver operating characteristic curve = .939) in CSF as significant predictors of CIS to RRMS conversion. In conclusion, our study suggests a trend towards elevated CSF IL-8 and CSF CXCL13 levels in CIS patients progressing to RRMS. These findings emphasize the importance of identifying prognostic markers to guide appropriate treatment strategies for individuals in the early stages of MS.
Keywords: Multiple Sclerosis, Relapsing-Remitting; Disease Progression; roztroušená skleróza; Chemokine CXCL13; progrese nemoci; Prognosis; chemokin CXCL13; Middle Aged; mužské pohlaví; CXCL13; Adult; mladý dospělý; interleukin-8; Demyelinating Diseases; Multiple Sclerosis; Young Adult; ženské pohlaví; prognóza; Humans; demyelinizační nemoci; biologické markery; lidé středního věku; relabující-remitující roztroušená skleróza; IL‐8; dospělí; Biomarkers; Female; Interleukin-8; biomarkers; clinically isolated syndrome; lidé; Male; multiple sclerosis